Analysis of The Adoption of The E-Asmara Application Technology in GresikRegency Using The Utaut 2 Model - Ayu Prania Arinda; Ahmad Mukhlason (Journal Research of Social Science, Economics, and Management, 2026)
The rapid advancement of information technology has driven the transformation of public services toward an electronic-based government system (e-government). The Regional House of Representatives (DPRD) of Gresik Regency, through its Secretariat, has launched the E-ASMARA (Electronic Public Aspiration) platform as a digital channel for citizens to submit aspirations and complaints. However, as of mid-2025, the utilization rate of the platform remains low, indicating potential barriers to public technology adoption. This study aims to analyze the factors influencing the acceptance and use of the E-ASMARA application among citizens of Gresik Regency by applying the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model, modified by adding two constructs: Trust and Satisfaction. The research employs a quantitative approach with data collected through offline questionnaires distributed to participants of the Legislative Regulation Socialization (Sosperda) activities conducted by DPRD members in each electoral district. Data were analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0 software. The analysis includes evaluating indicator validity and reliability (outer model), followed by examining inter-construct relationships (inner model) using the bootstrapping technique. The findings are expected to identify the dominant factors influencing citizens' behavioral intention and usage behavior toward the E-ASMARA application. The study also aims to provide strategic recommendations for the local government to enhance public trust, user satisfaction, and digital participation through the implementation of an inclusive and transparent e-government platform.